Pelaksanaan Jam Kerja Bagi Tenaga Kerja Wanita Terkait Dengan Upah Dan Kesejahteraan Di Bule-Bule Garment Surakarta - Rachma, Ghassani Aelsa; , Shalman Al-Farizy, S.H., M.kn (2017)
This study aims to investigate the implementation of the working hours of women who carried on by the Bule-Bule Garment Surakarta's company which have an impact on workes/laborers wage and welfare. Especially for women. The research method uses desciptive emperial jurisdiction. The sources of primary data is interviews and the secondary data is made from primary law and secondary law. The data were collected by interview, literature study and observation using qualitative analyzing. The result showed that in the implementation of hours of work done by the company Bule-Bule Garment Surakarta in accordance with the provisions of act No. 13 of 2003. The company's efforts Bule-Bule Garment Surakarta related to wages and benefits with granting rights in accordance with the work that has been done.